Importance of Echocardiography and Clinical “Red Flags” in Guiding Genetic Screening for Fabry Disease - Citro, Rodolfo; Prota, Costantina; Ferraioli, Donatella; Iuliano, Giuseppe; Bellino, Michele; Radano, Ilaria; Silverio, Angelo; Migliarino, Serena; Polito, Maria Vincenza; Ruggiero, Artemisia; Napoletano, Rosa; Bellizzi, Vincenzo; et al. (Frontiers in Cardiovascular Medicine, 2022)
INTRODUCTION: Aim of this study was to evaluate, in a metropolitan area not already explored, the prevalence of Anderson-Fabry disease, by genetic screening, in patients with echocardiographic evidence of left ventricular hypertrophy of unknown origin and “clinical red flags”. METHODS: From August 2016 to October 2017, all consecutive patients referring to our echo-lab for daily hospital practices with echocardiographic evidence of LVH of unknown origin in association with history of at least one of the classical signs and symptoms related to FD (neuropathic pain, anhidrosis/hypohidrosis, angiokeratomas, gastrointestinal problems, chronic kidney disease or cerebrovascular complications) were considered eligible for FD genetic screening program. Through dried blood spot testing, α-Gal A activity and analysis of the GLA gene were performed. RESULTS: Among 3360 patients underwent transthoracic echocardiography in our echo-lab during the study period 30 patients (0.89%; 19 males, mean age 58 ± 18.2 years) were selected. FD was diagnosed in 3 (10%) unrelated patients. Three different GLA gene mutations were detected, one of them [mutation c.388A>G (p.Lys130Glu) on the exon 3] never described before. Moreover, probands’ familiar genetic screening allowed the identification of 5 other subjects affected by FD. CONCLUSION: In a metropolitan area not previously investigated, among patients with LVH of unknown origin associated with other “red flags”, undergoing genetic screening, the prevalence of FD was very high (10%). Our results highlight the importance of an echocardiographic and clinical oriented genetic screening for FD in patients with uncommon cause of LVH.